Modulation of Nrf2 expression by targeting i-motif DNA - E. F. Warner; D. Guneri; M. A. O’Connell; C. J. MacDonald; Z. A. E. Waller (Communications Chemistry)
Abstract Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a key regulator of cell detoxification, which maintains homoeostasis in healthy cells and promotes chemoresistance in cancer cells. Controlling the expression of this transcription factor is therefore of great interest. There are many compounds that have been shown to induce Nrf2 expression, but ligands that can inhibit Nrf2 are scant. Herein we characterise an i-motif-forming sequence downstream of the Nrf2 promoter, which we hypothesised may regulate the expression of the gene. The Nrf2 i-motif was found to be stable at near-physiological conditions. We identified small molecule ligands that interact with this i-motif structure and one significantly upregulated Nrf2 mRNA expression, and one ligand reduced Nrf2 mRNA expression in human cancer cells. This is the first example of controlling the promoter of Nrf2 by targeting DNA structures and offers an alternative mode of action for the development of compounds to improve the chemotherapeutic responsiveness of existing treatments for cancer.